2017
DOI: 10.1080/19407963.2017.1297310
|View full text |Cite
|
Sign up to set email alerts
|

The causality relationships between tourism development and foreign direct investment: an empirical study in EU countries

Abstract: The main focus of this paper is the impact of foreign direct investment (FDI), official exchange rate and trade on international tourism using panel data of 27 countries over 1995-2014. The result based on the pooled mean group estimator of dynamic panels shows that there is no causality relationship between FDI and tourist receipts and a bidirectional causality relationship between real exchange rate, trade openness and tourist receipts and explains that FDI plays a significant role in expanding the tourism s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…The study findings suggest that further development in institutional quality and tourism activities will result in a positive way in the economy that induces foreign investors and increase possibilities for receiving additional FDI. These studies' findings are in line with Turan Katircioglu et al [33]; Perić and Radić [32]; Khoshnevis Yazdi, Nateghian and Sheikh Rezaie [67]; Buchanan, Le, and Rishi [19]; Jushi et al [164]. About CS-ARDL, the study findings also ascertain positive relations between institutional quality, tourism, and inflows of FDI in BIMSTEC nations, especially in the long run.…”
Section: Discussionsupporting
confidence: 84%
“…The study findings suggest that further development in institutional quality and tourism activities will result in a positive way in the economy that induces foreign investors and increase possibilities for receiving additional FDI. These studies' findings are in line with Turan Katircioglu et al [33]; Perić and Radić [32]; Khoshnevis Yazdi, Nateghian and Sheikh Rezaie [67]; Buchanan, Le, and Rishi [19]; Jushi et al [164]. About CS-ARDL, the study findings also ascertain positive relations between institutional quality, tourism, and inflows of FDI in BIMSTEC nations, especially in the long run.…”
Section: Discussionsupporting
confidence: 84%
“…The unidirectional causality is parallel with Kaushal and Pathak (2015) who found growth rate in GDP Granger caused trade openness. One-way causal relation from exchange rate to trade openness is parallel with Yazdi et al (2017)…”
Section: Discussionmentioning
confidence: 99%
“…Cointegration test results detailed that long term relation prevails between FDI, tourism value and tourist arrivals in Saudi Arabia. Yazdi et al (2017) found no causality between tourist receipts and foreign direct investment and found two-way causality among trade openness, real exchange rate and tourist receipts and concluded that FDI significantly expands the tourism industry in European countries. Kaur and Sarin (2016) used time series models for the time period spanning from 1991 to 2014 and found one directional long term causality evidence from tourism activities to India's economic growth.…”
Section: Tourismmentioning
confidence: 93%
“…A positive relationship between FDI and tourism has been found by number of previous researchers (Alam et al, 2015, 2016; Chen, 2017; Craigwell & Moore, 2007; Katricioglu, 2011; Kaur & Sarin, 2016; Kumar, 2014; Nunkoo & Seetanah, 2018; Ohlan, 2017; Othman et al, 2012; Perić & Radıć, 2015; Ravinthirakumaran et al, 2019; Salleh et al, 2015; Samimi et al, 2013; Satrovic & Muslija, 2018). On the other hand, few studies found negative relationship between FDI and tourism (Jing et al, 2018; Khoshnevis Yazdi et al, 2017; Petanlar et al, 2016), while Siddiqui and Siddiqui (2019) found no relationship between FDI and tourism. There are very few studies which analyze the linear and nonlinear relationship between FDI, exchange rate, and tourism (Kumar et al, 2020; Meo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…FDI helps in bringing finance, technology transfer, development of infrastructure, employment creation, and stimulates economic growth. Along with a number of benefits that FDI brings in the host country it also plays a prominent role in developing tourism industry (Khoshnevis Yazdi et al, 2017). Tourism and FDI are two important forces affecting different countries of the world.…”
Section: Introductionmentioning
confidence: 99%